Infarct size, inflammatory burden and admission hyperglycemia in diabetic patients with acute myocardial infarction treated with SGLT2-inhibitors: a multicenter international registry. (3rd October 2022) - Sansonetti, A; Paolisso, P; Bergamaschi, L; Santulli, G; Gallinoro, E; Cesaro, A; Gragnano, F; Sardu, C; Mileva, N; Mauro, C; Vassilev, D; Marfella, R; et al.
Abstract: Background: Sodium-glucose co-transporter 2 inhibitors (SGLT2-I) currently receive intense clinical interest in patients with and without diabetes mellitus (DM) with pleiotropic beneficial effects. Nowadays, the inflammation response in the setting of acute myocardial infarction (AMI) has been proposed as a potential pharmacological intervention target. In this setting, we tested the hypothesis that the SGLT2-I displays anti-inflammatory effect along with glucose-lowering properties. We investigated the relationship between stress hyperglycemia, inflammation burden and infarct size in a cohort of type 2 diabetic AMI patients treated with SGLT2-I versus other oral anti-diabetic (OAD) agents alone. Methods: In this multicenter international registry, all diabetic patients with AMI treated with percutaneous coronary intervention (PCI) between 2018 and 2021 were enrolled. Based on the admission anti-diabetic therapy, patients were divided into those receiving SGLT2-I versus other OAD agents alone. Patients on insulin therapy alone or combined with OAD agents were excluded from the study. The following inflammatory markers were evaluated at different time points: total white blood cell, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and neutrophil-to-platelet ratio (NPR), C-reactive protein. Infarct size was assessed by peak troponin levels and echocardiographic parameters. Results: The final study population consisted of 583 patients hospitalized for AMI (both STEMI and NSTEMI) classified as SGLT2-I users (n=98) versus other OAD agents alone (n=485). Admission hyperglycemia was more prevalent among the other OAD agents group. Reduced infarct size was detected in patients treated with SGLT2-I compared to those treated with other OAD agents alone. Both at admission, and after 24 hours, inflammatory indices were significantly higher in patients treated with other OAD agents alone, with a significant increase in neutrophils levels at 24 hours, compared to the SGLT2-I group. In multivariate analysis, SGLT2-I emerged as a significant predictor of reduced inflammatory response (OR 0.45, 95% CI 0.27–0.75, p=0.002), together with peak troponin values, independently of age, admission creatinine values and admission glycemia. Conclusions: Type 2 Diabetic patients hospitalized for AMI and receiving SGLT2-I exhibited modest inflammatory response and myocardial damage/infarct size compared to other OAD agents alone, independently of glucose-metabolic control. Our findings pave the way for new pathophysiological and therapeutic insights regarding the cardioprotective effect of SGLT2-I in the setting of coronary artery disease. Funding Acknowledgement: Type of funding sources: None.